EXPERIENCE OF INTRAVENOUS INJECTION OF NORMAL HUMAN IMMUNOGLOBULIN IN A PATIENT WITH KAWASAKI SYNDROME - T. V. Sleptsova; E. I. Alexeeva; T. M. Bzarova; R. V. Denisova; K. B Isaeva; E. G. Chistyakova; A. N. Fetisova; O. L. Lomakina (Union of pediatricians of Russia, 2014)
The article presents a case of late diagnosis of cutaneomucosal lymphonodular syndrome (Kawasaki syndrome). The child featured fever, mucosal lesion (conjunctivitis, stomatitis), rash, thick edemas on arms and feet, arthritis and coronaritis. Initial therapy proved ineffective. Pathogenetic therapy, which proved to be rather effective, was prescribed after diagnosis was confirmed. The authors present a case of successful use of normal human immunoglobulin for intravenous injections in the dose of 2 g/kg of body weight per course in combination with acetylsalicylic acid in the dose of 80 mg/kg per day. Body temperature decreased down to subfebrile figures and foot pain attenuated as early as after 1 day of treatment. Fever, rash, stomatitis and conjunctivitis terminated, edemas of limbs and arthritic manifestations attenuated considerably and laboratory parameters of disease activity normalized after 1 week (ESR and CRP). Inflammation of coronary arteries terminated after 3 weeks. No adverse events in the setting of immunoglobulin therapy were observed.